China's photovoltaic power development under policy incentives: A system dynamics analysis. (15th December 2015) - Guo, Xiaodan; Guo, Xiaopeng
Abstract: Recently China has brought out several incentive policies to break high-cost limitation and stimulate investment in photovoltaic industry. Under this favorable policy environment, PV power is undoubtedly facing enormous development opportunities. Firstly, after analyzing current policy environment and interactions between involved variables, a simulation model of China's PV power development was built using system dynamics methodology considering both economic and technical factors. Secondly, sensitivity analyses are made to analyze the sensitivities of key variables and the effectiveness of relevant policies. The simulated results of generation, investment and capacity during 2012–2032 indicate the future developing trend, and evaluate the rationality and effect of incentive policies. The model allows an understanding of PV power's long-term development pattern under China's latest incentive policies, thus helping to provide reference for policy-making institutions. Highlights: We analyze China's latest incentive policies of PV power industry. We simulate the long-term development pattern of China's PV power. China's distributed PV industry mainly benefits from subsidy not power generation. Investment surge will accelerate the growth of China's installed PV capacity. Investment subsidy is necessary unless technological breakthroughs take place.